The Manchester Triage System (MTS): a score for emergency management of patients with acute gastrointestinal bleeding - Nguyen-Tat, Marc; Cornelius, Constantin; Hoffman, Arthur; Tresch, Achim; Krey, Joerg; Kiesslich, Ralf; Galle, Peter Robert; Rey, Johannes Wilhelm (Zeitschrift für Gastroenterologie, 2018)
Background Suspected gastrointestinal (GI) bleeding is a common initial diagnosis in emergency departments. Despite existing endoscopic scores to estimate the risk of GI bleeding, the primary clinical assessment of urgency can remain challenging. The 5-step Manchester Triage System (MTS) is a validated score that is often applied for the initial assessment of patients presenting in emergency departments.Methods All computer-based records of patients who were admitted between January 2014 and December 2014 to our emergency department in a tertiary referral hospital were analyzed retrospectively. The aim of our retrospective analysis was to determine if patient triage using the MTS is associated with rates of endoscopy and with presence of active GI bleeding.Results In summary, 5689 patients with a GI condition were treated at our emergency department. Two hundred eighty-four patients (4.9 %) presented with suspected GI bleeding, and 165 patients (58 %) received endoscopic diagnostic. Endoscopic intervention for hemostasis was needed in 34 patients (21 %). In patients who underwent emergency endoscopy, triage into MTS categories with higher urgency was associated with higher rates of endoscopic confirmation of suspected GI bleeding (79 % of patients with MTS priority levels 1 or 2, 53 % in level 3 patients, and 40 % in levels 4 or 5 patients; p = 0.024).Conclusions The MTS is an established tool for triage in emergency departments and could have a potential to guide early clinical decision-making with regards to urgency of endoscopic evaluation in patients with suspected GI bleeding.
Keywords: gastrointestinal bleeding; GI hemorrhage; Manchester Triage System (MTS); endoscopy; bleeding risk